2021
DOI: 10.3390/microorganisms9081738
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Full Vaccination with mRNA BNT162b2 on SARS-CoV-2 Infection: Genomic and Subgenomic Viral RNAs Detection in Nasopharyngeal Swab and Saliva of Health Care Workers

Abstract: SARS-CoV-2 infection was monitored in 1898 health care workers (HCWs) after receiving full vaccination with BNT162b2. Untill 30 June 2021, 10 HCWs tested positive for SARS-CoV-2 using real time RT-PCR, resulting in a 4-month cumulative incidence of 0.005%. The infection was mildly symptomatic in six (60%) and asymptomatic in four (40%) individuals. Among the infected HCWs, eight consenting individuals provided paired NPS and saliva during the course of infection, for the purpose of the analysis performed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…In our study we observed the occurrence of infection in vaccinated individuals with high viral titers suggestive of efficient viral replication. This is supported by previous studies that detected active viral replication in SARS-CoV-2-positive vaccinated individuals by analysis of subgenomic viral RNA [ 20 , 21 ]. Nonetheless, similarly to our results, the frequency of infection post-vaccination was low, the symptomatology was really mild and, importantly, the viral load rapidly declined [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In our study we observed the occurrence of infection in vaccinated individuals with high viral titers suggestive of efficient viral replication. This is supported by previous studies that detected active viral replication in SARS-CoV-2-positive vaccinated individuals by analysis of subgenomic viral RNA [ 20 , 21 ]. Nonetheless, similarly to our results, the frequency of infection post-vaccination was low, the symptomatology was really mild and, importantly, the viral load rapidly declined [ 20 , 21 ].…”
Section: Discussionsupporting
confidence: 85%
“…This is supported by previous studies that detected active viral replication in SARS-CoV-2-positive vaccinated individuals by analysis of subgenomic viral RNA [ 20 , 21 ]. Nonetheless, similarly to our results, the frequency of infection post-vaccination was low, the symptomatology was really mild and, importantly, the viral load rapidly declined [ 20 , 21 ]. In particular, in agreement with our data, in the one case report, the speed of viral decay was significantly faster compared to a reference group of non-vaccinated individuals [ 21 ].…”
Section: Discussionsupporting
confidence: 85%
“…However this is not practical in most diagnostic laboratories, and importantly, may not be sensitive enough to detect low levels of potential infectivity [7,11] . This has led to a number of other molecular indicators such as detection of subgenomic RNAs or negative sense RNA being proposed as possible markers of whether an individual is likely to be infectious or not to aid in the control of SARS-CoV-2 [7,12-14] . The rationale being that these molecules are generated intracellularly by the virus during virus replication.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have proposed using subgenomic RNA or negative sense SARS-CoV-2 RNA as a marker of active replication of the virus within an individual [7,11,13,14,24] . However, we recently reported that we were able to detect subgenomic RNA and negative sense RNA in samples up to 17 days post infection, and that subgenomic RNAs are relatively stable and likely persist in samples protected by the double membrane structures created during the replication of the virus in the cytoplasm of SARS-CoV-2 infected cells [23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation